Very Low Efficiency of Direct Reprogramming of Astrocytes Into Neurons in the Brains of Young and Aged Mice After Cerebral Ischemia - Gresita, Andrei; Glavan, Daniela; Udristoiu, Ion; Catalin, Bogdan; Hermann, Dirk M.; Popa-Wagner, Aurel (Frontiers in Aging Neuroscience, 2019)
After cerebral ischemia, the ratio between astroglial cells and neurons in the neurovascular unit is disrupted in the perilesional area. We hypothesized that restoring the balance within the neurovascular unit may lead to an improved neurorestoration after focal ischemia. Recently, an innovative technology has been invented to efficiently convert proliferating astroglial cells into neurons in the injured young brain. However, the conversion efficacy of this technology has not been explored in the post-stroke brains of the aged rodents. To this end, we used a retroviral delivery system encoding the transcription factor Ngn2 alone or in combination with the antiapoptotic factor Bcl-2 to target proliferating astrocytes in the neocortex of young and aged mice after cerebral ischemia. Successful direct in vivo reprogramming of reactive glia into neuroblasts and mature neurons was assessed by cellular phenotyping. We found that the conversion efficacy of proliferating astrocytes into neurons after cerebral ischemia in young and aged mice is disappointingly low, most likely because the therapeutic vectors carrying the conversion gene are engulfed by phagocytes shortly after intracortical administration. We conclude that other viral vectors and combinations of transcription factors should be employed to improve the efficacy of glia-to-neuron conversion after stroke in young and aged rodents.